2011
DOI: 10.1124/dmd.110.037457
|View full text |Cite
|
Sign up to set email alerts
|

Human Pharmacokinetic Prediction of UDP-Glucuronosyltransferase Substrates with an Animal Scale-Up Approach

Abstract: ABSTRACT:The aim of the current study was to evaluate the accuracy of allometric scaling methods for drugs metabolized by UDP-glucuronosyltransferases (UGTs), such as ketoprofen, imipramine, lorazepam, levofloxacin, zidovudine, diclofenac, furosemide, raloxifene, gemfibrozil, mycophenolic acid, indomethacin, and telmisartan. Human plasma clearance (CL) predictions were conducted from preclinical in vivo data by using multiple-species allometry with the rule of exponents and single-species allometric scaling (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 33 publications
2
29
1
Order By: Relevance
“…However, where comparisons were possible, the mouse PK for the compounds used in our studies were comparable to the literature. For example, gemfibrozil PK study in mouse reported a bioavailability of 73% which was similar to the 60% that we report in our studies (36) .…”
Section: Discussionsupporting
confidence: 74%
“…However, where comparisons were possible, the mouse PK for the compounds used in our studies were comparable to the literature. For example, gemfibrozil PK study in mouse reported a bioavailability of 73% which was similar to the 60% that we report in our studies (36) .…”
Section: Discussionsupporting
confidence: 74%
“…The very minor component being metabolized is represented by a pharmacologically inactive acyl glucuronide, which is the only metabolite that has been identified in human plasma and urine and accounts for approximately 11% of total radioactivity in plasma. Formation of the glucuronide metabolite in humans can best be predicted preclinically using canine data (Deguchi et al, 2011). The P450 enzymes are not involved in the metabolism of telmisartan, and an inhibition of CYP2C9 function has only been observed at very high and probably supratherapeutic concentrations .…”
Section: Metabolismmentioning
confidence: 99%
“…UGT1A8 and UGT1A10, isozymes that are absent in the human liver, are thought to glucuronidate raloxifene mainly in the intestine and lead to extremely low F (Kemp et al, 2002;Jeong et al, 2005). F of raloxifene in rats and dogs was originally reported as 39 and 17%, respec-tively (Lindstrom et al, 1984), and have been recently reported as 4 and 0%, respectively (Deguchi et al, 2011). The UGT isozymes responsible for the glucuronidation of raloxifene and its intestinal and hepatic availabilities (Fg and Fh, respectively) in preclinical animals have not been investigated adequately.…”
Section: Introductionmentioning
confidence: 99%